Growth Forecast Errors and Fiscal Multipliers - Blanchard, Olivier (IMF Working Papers; Working Paper ;, 2013)
This paper investigates the relation between growth forecast errors and planned fiscal consolidation during the crisis. We find that, in advanced economies, stronger planned fiscal consolidation has been associated with lower growth than expected, with the relation being particularly strong, both statistically and economically, early in the crisis. A natural interpretation is that fiscal multipliers were substantially higher than implicitly assumed by forecasters. The weaker relation in more recent years may reflect in part learning by forecasters and in part smaller multipliers than in the early years of the crisis.